Prevention of Hepatitis B Virus (HBV) Is Essential to Avoid Chronic Liver Disease - Haradhan Kumar Mohajan (Innovation in Science and Technology, 2025)
Hepatitis B is a viral infection that is caused by hepatitis B virus (HBV), which becomes a severe public health problem worldwide. It is a short-term acute illness or a lifelong chronic infection that may be a cause of life-threatening liver cirrhosis, liver failure, liver cancer, and hepatocellular carcinoma (HCC). Persistence of HBV infection may remain for six months or more indicates chronic liver infection. Hepatitis B is transmitted by body fluids, such as blood, semen, vaginal secretions of hepatitis B patient; by sharing shaving razors, needles, syringes, etc. contaminated with HBV; having any kind of unprotected sex, such as vaginal, anal and oral sex with HBV infected patients; HBV infected mother to new born babies; use of surgical and dental tools of contaminated with HBV; use of tattooing or body piercing equipment of HBV patient, and so on. The HBV is endemic in Asia, Pacific Islands, Africa, Southern Europe, and Latin America. An attempt has been taken to discuss the HBV infection, its treatment, and prevention through the vaccination.